Exploring the Personality Traits of Portugal as a Tourist Destination: Perspective of the Czech Market - Guerreiro, Manuela; Agapito, Dora; Pech, Matěj (Journal of Tourism, Sustainability and Well-being, 2015)
The personality of a destination is vital to build a coherent destination brand and strengthen the place identity. Furthermore, brand personality appears in literature as a strategic axis that can be explored by tourist destinations in order to differentiate themselves from competitors. Since a brand encompasses not only functional but also symbolic elements, its image, as perceived by consumers, can be assessed with respect to both its functional and psychological components. Hence, this exploratory study investigates the brand personality of Portugal as a tourist destination, from the perspective of the Czech market, through a destination image approach. The online survey instrument included open-ended items to depict functional and psychological destination features and additional questions to characterize the profile of a sample of Czech university students. The main findings of this research highlight positive personality traits that are related to the brand of Portugal, which suggest its potential as a vacation destination for the Czech market under study.